Teachers' Challenges in Teaching Science Process Skills to Seventh Grade Students: Kendala Guru dalam Melatihkan Keterampilan Proses Sains Siswa Kelas VII - Hayazee, Fadilah; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Science process skills are essential in science education to foster students’ understanding and application of scientific concepts through practical activities. Specific Background In Indonesian junior high schools, practical work is a key strategy to develop these skills, yet many students struggle to achieve optimal competency. Knowledge Gap Limited studies have explored specific obstacles faced by teachers and students during the training of science process skills in real classroom settings, particularly in MTs or equivalent institutions. Aims This study aims to identify the challenges encountered in fostering science process skills among seventh-grade students at MTs Terpadu Mardlatillah. Results Using a qualitative descriptive method with data triangulation (questionnaires, documentation, and interviews) and Miles & Huberman’s analysis model, the study examined eight indicators of science process skills. Findings revealed four main challenges: difficulty in determining variables, absence of experimental setup images, inability to analyze data and draw conclusions, and low confidence in presenting results. Novelty This research provides a detailed mapping of science process skill challenges in the context of Islamic junior high school practical activities, integrating both teacher and student perspectives. Implications Addressing these issues is crucial to prevent further skill gaps and to improve practical science education strategies in similar educational contexts. Highlights : Identification of four key challenges in training science process skills Use of qualitative descriptive method with data triangulation Contextual focus on practical science learning in Islamic junior high school Keywords : Science Process Skills, Practical Work, Junior High School, Qualitative Research, Learning Challenges